Trends transnationalization of the world economy in the context of globalization - Ермекова, Ж. (Journal of Economic Research & Business Administration, 2017)
Questions of economic transnationalization gained its relevance due to the rapid development of the relationship between the national economy and global economic processes, the essence of which consists in the intensive development of economic globalization. The study of these issues involved a large number of researchers. However, interest in this topic is not only not disappeared, but has taken on new dimensions. Today, we can speak of two main views: on the one hand, globalization encourages the economy to self-development, as a precondition for the preservation of its sovereignty, but on the other - it is a prerequisite to use the economies of developing countries as a kind of convenient springboard for deployment of new production facilities belonging to the developed countries. And in order to take its rightful place in these circumstances, the company based on global trends and its own peculiarities should develop and ensure the implementation of evidencebased economic strategy. The centerpiece of the government’s economic strategy and business takes transnationalization of capital and labor.